Genetic diversity does not explain variation in extra‐pair paternity in multiple populations of a songbird. (12th May 2015) - Liu, I. A.; Johndrow, J. E.; Abe, J.; Lüpold, S.; Yasukawa, K.; Westneat, D. F.; Nowicki, S.
Abstract Many songbirds are socially monogamous but genetically polyandrous, mating with individuals outside their pair bonds. Extra‐pair paternity (EPP) varies within and across species, but reasons for this variation remain unclear. One possible source of variation is population genetic diversity, which has been shown in interspecific meta‐analyses to correlate with EPP but which has limited support from intraspecific tests. Using eight populations of the genetically polyandrous red‐winged blackbird (Agelaius phoeniceus), including an island population, we investigated whether population‐level differences in genetic diversity led to differences in EPP. We first measured genetic diversity over 10 microsatellite loci and found, as predicted, low genetic diversity in the island population. Additional structure analyses with multilocus genotypes and mtDNA showed the island population to be distinct from the continental populations. However, the island population's EPP rate fell in the middle of the continental populations' distribution, whereas the continental populations themselves showed significant variation in EPP. This result suggests that genetic diversity by itself is not a predictor of EPP rate. We discuss reasons for the departure from previous results, including hypotheses for EPP that do not solely implicate female‐driven behaviour.